PENGARUH BAURAN PEMASARAN (MARKETING MIX) TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA L’CHEESE FACTORY KECAMATAN SUKAJADI KOTA PEKANBARU - Syafriani, Septia; ', Caska; Syabrus, Hardisem (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This research was motivated by consumers are now beginning to be selective and smart in choosing a product, so they will get the usefulness or benefits they seek from a product such as a product of L'Cheese Factory. The purpose of this study was to determine and analyze how much influence marketing mix on consumer purchasing decisions at L'Cheese Factory District of Sukajadi Pekanbaru. The population in this study is the customer L'Cheese Factory Pekanbaru grand total is 65 with a sample of 39 people. Based on the analysis concluded that the known value of significance at the table coeffisients 0,000 less than the critical value of 0.05. Then obtained 0.000 <0.05 and these results show that the Marketing Mix (Marketing Mix) effect on Consumer Purchase Decision on L'Cheese Factory Pekanbaru. Regression model in this study is Y = -47 266 + 1.531X1 + 1.040X2 + 1.035X3 + 1.451X4, the magnitude of the constant coefficient is -47 266, which means if the marketing mix (marketing mix) and the purchase decision has no effect, the size of the customer's decision is -47 266. Regression coefficient value product is +1531, meaning if the product has increased by 1%, then the customer's decision will also be increased by 1,531. The coefficient of price is +1040, meaning if the price increased by 1%, then the customer's decision will also be increased by 1,040. A coefficient value is +1035, that if the place is increased by 1%, then the customer's decision will also be increased by 1,035 and the promotion of the regression coefficient is +1451, meaning if the sale increased by 1%, then the customer's decision will also be increased by 1,451 , Judging from R Square of 0.472, indicating that the independent variables used in this study can affect the dependent variable 47.2%. Thus it can be said that the ability of independent variables in influencing the dependent variable is influential.Key Words : Product, Price, Place, Promotion, and Purchase Decision